Renal tubule-specific Atgl deletion links kidney lipid metabolism to glucagon-like peptide 1 and insulin secretion independent of renal inflammation or lipotoxicity - Maria F. Fernandes; Juan J. Aristizabal-Henao; Phillip M. Marvyn; Iman M'Hiri; Meghan A. Wiens; Monica Hoang; Manuel Sebastian; Renato Nachbar; Philippe St-Pierre; Kalsha Diaguarachchige De Silva; Geoffrey A. Wood; Jamie W. Joseph; et al. (Elsevier, 2024)
Objective: Lipotoxic injury from renal lipid accumulation in obesity and type 2 diabetes (T2D) is implicated in associated kidney damage. However, models examining effects of renal ectopic lipid accumulation independent of obesity or T2D are lacking. We generated renal tubule-specific adipose triglyceride lipase knockout (RT-SAKO) mice to determine if this targeted triacylglycerol (TAG) over-storage affects glycemic control and kidney health. Methods: Male and female RT-SAKO mice and their control littermates were tested for changes in glycemic control at 10-12 and 16-18 weeks of age. Markers of kidney health and blood lipid and hormone concentrations were analyzed. Kidney and blood lysophosphatidic acid (LPA) levels were measured, and a role for LPA in mediating impaired glycemic control was evaluated using the LPA receptor 1/3 inhibitor Ki-16425. Results: All groups remained insulin sensitive, but 16- to 18-week-old male RT-SAKO mice became glucose intolerant, without developing kidney inflammation or fibrosis. Rather, these mice displayed lower circulating insulin and glucagon-like peptide 1 (GLP-1) levels. Impaired first-phase glucose-stimulated insulin secretion was detected and restored by Exendin-4. Kidney and blood LPA levels were elevated in older male but not female RT-SAKO mice, associated with increased kidney diacylglycerol kinase epsilon. Inhibition of LPA-mediated signaling restored serum GLP-1 levels, first-phase insulin secretion, and glucose tolerance. Conclusions: TAG over-storage alone is insufficient to cause renal tubule lipotoxicity. This work is the first to show that endogenously derived LPA modulates GLP-1 levels in vivo, demonstrating a new mechanism of kidney-gut-pancreas crosstalk to regulate insulin secretion and glucose homeostasis.